Rationality of standardization by local authority of extension for terrace house / Nor Idayu Nordin - Nordin, Nor Idayu (2002)
Extensions of terrace house are a normal scenario in every residential scheme area. Since the house owner paid their booking fees for the house their had a target and an idea to extent their house. And the result, varying designs and haphazard extensions, which sometimes cause a house to stick out, like a “sore thumb” in the residential scheme. To control this situation, Housing and Local Government announced to control this with standardized all the renovation and extension of terrace house on 1994. Following the announcement, the developer would have to be submitted the extensions plans together with the main building plans to local authorities. House owner who want to extent their house, can by this extensions plans from the local authority. Although this procedure can gives an extra advantage to the house owner, they didn’t accept this procedure because they think this procedure will restrict their design. Unluckily in the practically, this procedure didn’t to execute because following the Uniform Building By-Laws 1974 only the qualified person can submit the plan for approval. So, the house owner can chose their qualified person to submit the plans for approval. But they must following the acts standard to do the extension of terrace house. For local authorities they used the acts and policy for suitable with their area as a guideline and some of the local authority have their own handbook for extensions work for guide the house owner who want to make an extensions of terrace house. So, with policy availability, have a different standardized of extensions with different local authority (council area) Besides following the standard, the house owner must following the procedure by council to gets a building extensions plans approval from the local authority. This standardization gives a pro and contra to who directly or indirectly involve in extension works either from parties whose must to enforce or parties who must following this standardization. The purpose of this dissertation is to know the rationality of the standardization by local authority of extensions for terrace house.